Study of clinical significance and histopathological correlation of serum β- hCG level - Mulla, Faruq Ibrahimbhai; Inaniya, Kailash Sukhram (International Journal of Research in Medical Sciences, 2017)
Background: β-hCG is a marker useful in diagnosis of gestational trophoblastic disease (GTD), ectopic gestation (EG), spontaneous abortion (SA) and malignant germ cell tumors (MGCT) and it is helpful to clinician as an excellent tumor marker. It is useful to monitor treatment whether tumor is responding to treatment or the disease is progressing. Methods: β-hCG is a marker useful in diagnosis of gestational trophoblastic disease (GTD), ectopic gestation (EG), spontaneous abortion (SA) and malignant germ cell tumors (MGCT) and it is helpful to clinician as an excellent tumor marker. It is useful to monitor treatment whether tumor is responding to treatment or the disease is progressing. Results: p value is highly significant in Gestational Trophoblastic Diseases, EG and SA, as p value is < 0.005 in all these three categories. But in case of MGCT it is 0.452 which is not significant because study group was very small and one case who developed recurrence affected the value significantly. These findings suggest that β-hCG has definitive prognostic role (p value<0.005) in GTD, EG and SA. Conclusions: ELISA is rapid, sensitive, reliable and cost effective test for measurement of β-hCG. Pre-and post-therapeutic β-hCG serum levels seem to be useful in the therapy monitoring of trophoblastic gynaecological conditions i.e. GTD, EG and SA.